The synergistic activity of SBC3 in combination with Ebselen against Escherichia coli infection - Chen, Hao; Lu, Qianqian; An, Haoyue; Li, Juntong; Shen, Shuchu; Zheng, Xi; Chen, Wei; Wang, Lu; Li, Jihong; Du, Youqin; Wang, Yueqing; Liu, Xiaowen; et al. (Frontiers in Pharmacology, 2022)
Escherichia coli ranks as the number one clinical isolate in the past years in China according to The China Antimicrobial Surveillance Network (CHINET), and its multidrug-resistant (MDR) pathogenic strains account for over 160 million cases of dysentery and one million deaths per year. Here, our work demonstrates that E. coli is highly sensitive to the synergistic combination of SBC3 [1,3-Dibenzyl-4,5-diphenyl-imidazol-2-ylidene silver (I) acetate] and Ebselen, which shows no synergistic toxicity on mammalian cells. The proposed mechanism for the synergistic antibacterial effect of SBC3 in combination with Ebselen is based on directly inhibiting Escherichia coli thioredoxin reductase and rapidly depleting glutathione, resulting in the increase of reactive oxygen species that cause bacterial cell death. Furthermore, the bactericidal efficacy of SBC3 in combination with Ebselen has been confirmed in mild and acute peritonitis mice. In addition, the five most difficult to treat Gram-negative bacteria (including Escherichia coli, Acinetobacter baumannii, Enterobacter cloacae, Klebsiella pneumoniae, and Pseudomonas aeruginosa) are also highly sensitive to a synergistic combination of SBC3 and Ebselen. Thus, SBC3 in combination with Ebselen has potential as a treatment for clinically important Gram-negative bacterial infections.